Understanding the factors that affect the appropriateness of rheumatology referrals - Eline van den Broek-Altenburg; Adam Atherly; Nick Cheney; Teresa Fama (BMC, 2021)
Abstract Background Reducing inappropriate referrals to specialists is a challenge for the healthcare system as it seeks to transition from volume to value-based healthcare. Given the projection of a severe shortage of rheumatologists in the near future, innovative strategies to decrease demand for rheumatology services may prove more fruitful than increasing the supply of rheumatologists. Efforts to increase appropriate utilization through reductions in capacity may have the unintended consequence of reducing appropriate care as well. This highlights the challenges in increasing the appropriate use of high cost services as the health system transitions to value based care. The objective of this study was to analyze factors affecting appropriateness of rheumatology services. Methods This was a cross-sectional study of patients receiving Rheumatology services between November 2013 and October 2019. We used a proxy for "appropriateness": whether or not there was any follow-up care after the first appointment. Results from regression analysis and physicians' chart reviews were compared using an inter-rater reliability measure (kappa). Data was drawn from the EHR 2013-2019. Results We found that inappropriate referrals increased 14.3% when a new rheumatologist was hired, which increased to 14.8% after wash-out period of 6 months; 15.7% after 12 months; 15.5% after 18 months and 16.7% after 18 months. Other factors influencing appropriateness of referrals included severity of disease, gender and insurance type, but not specialty of referring provider. Conclusions Given the projection of a severe shortage of rheumatologists in the near future, innovative strategies to decrease demand for rheumatology services may prove more fruitful than increasing the supply of rheumatologists. Innovative strategies to decrease demand for rheumatology services may prove more fruitful than increasing the supply of rheumatologists. These findings may apply to other specialties as well. This study is relevant for health care systems that are implementing value-based payment models aimed at reducing inappropriate care.